Advanced/hybrid thermal energy storage technology: material, cycle, system and perspective. (July 2021) - Ding, Zhixiong; Wu, Wei; Leung, Michael
Abstract: Thermal energy storage (TES) technology is playing an increasingly important role in addressing the energy crisis and environmental problems. Various TES technologies, including sensible-heat TES, latent-heat TES, and thermochemical TES, have been intensively investigated in terms of principles, materials, and applications. A bibliometric study between 2000 and 2019 is conducted to show the evolution of TES technology and to predict future trends. While the existing studies are focused on basic TES, advanced/hybrid TES technologies have attracted increasing interest and demonstrated outstanding merits in overcoming the disadvantages of basic TES. To promote the advanced/hybrid TES technologies, a review is conducted to summarize the progress in advanced storage cycles, hybrid storage materials, and hybrid storage systems. The comprehensive literature review indicated that latent-heat TES has been the focus in the past years. While thermochemical TES and its hybrid TES technologies show the greatest research potential and become an emerging hot topic. Each advanced/hybrid TES technology has a certain improvement over basic TES, such as increasing the energy storage density or energy storage efficiency, reducing the charging temperature, enhancing the thermal conductivity of the sorbents, stabilizing the discharging temperature, or improving the performance of the integrated systems. Apart from the published results, some potential advanced/hybrid TES technologies are put forward to further enrich the TES family and to improve the TES performance. This work aims to facilitate the advancement of advanced/hybrid TES technologies. Graphical abstract: Image 1 Highlights: Classification, principle, materials of basic thermal energy storage are presented. A bibliometric analysis is conducted to show the research status. The advanced/hybrid TES technologies are comprehensively reviewed and evaluated. Potential novel technologies and future perspectives are proposed.